ORDENAMIENTO TERRITORIAL Y FORMACIÓN DE LAS PRIMACÍAS EN LAS SABANAS DE BOLÍVAR EN EL SIGLO XIX - Támara Gómez, Edgardo (Historia Caribe, 2008)
Estudio del proceso histórico sobre la primacía político-económica de Sincelejo ante sus coetÆ- neas Corozal y Chinœ, en la zona de Sabanas del antiguo Bolívar. En consecuencia, se siguen las dinÆmicas económicas de la subregión (tabaco, aguardiente, ganadería), los cambios educativos, el papel de la administración pœblica de la Øpoca y el papel del impuesto subsidiario en la vialida de la zona y su economía. PALABRAS CLAVE Sabanas de Bolívar, Sincelejo, Corozal, Chinœ, primacías, geografía política, microhistoria, desarrollo regional, división territorial, siglo XIX en la costa norte de Colombia. ABSTRACT Study of the historical process of the politico-economic primacy of Sincelejo in front of their contemporary Corozal and Chinœ,in the area of Savannas of old Bolívar.It begins clarifying the geographical and historical conceptualization and, then, the territorial process of north Colombian Costa is schematized inside the national context of the process of territorial national classification. Subsequently, the economic dynamicsof the subregión (tobacco, liquor, cattle raising) are studied, altogether with the educational changes, the paper of the public administration of that period and the sale that the subsidiary played in the construction of the Public roads of the area and their economy. KEY WORDS Savannas of Bolívar, Sincelejo, Corozal, Chinœ, primacies, political geography, microhistoria, regional development, territorial division, XIX century in the north coast of Colombia.